Government's Unequal Attentiveness to Citizens' Political Priorities. Issue 4 (9th September 2016) - Flavin, Patrick; Franko, William W.
Abstract: An accumulation of evidence suggests citizens with low incomes have relatively little influence over the policy decisions made by lawmakers in the United States. However, long before elected officials are asked to cast a final vote on a bill's passage, an equally important decision has already been made: the decision for government to focus its limited attention and agenda space on the issue at all. Therefore, it is possible that political inequality is infused earlier in the policymaking process at the agenda‐setting stage if the issues held important by some citizens are given attention while the issues held important by others are not. To investigate this question, we develop novel state‐level measures of citizens' issue priorities and find sizable differences in which issues poor and rich citizens think are most important and deserving of government attention. We then use bill introduction data from state legislatures to measure government attention and uncover evidence that state legislators are less likely to act on an issue when it is prioritized by low‐income citizens as compared to affluent citizens. These findings have important implications for our understanding of political equality and the functioning of American democracy.